Analysis of the learning model implementation learning cycle 5e in science learning - Siti Kulsum; Yanti Rusdianti; Novita Vandrianur; Eneng Fitri; Siti Mardiana (STKIP Persada Khatulistiwa Sintang, 2026)
Science learning at the junior high school level plays an important role in developing students’ science process skills as the foundation of scientific literacy. However, classroom practices still tend to emphasize content mastery rather than learning processes and systematic skill development. This study aimed to analyze the implementation of the 5E Learning Cycle model in acid–base learning, focusing on the development of students’ science process skills at each learning stage. This research employed a descriptive qualitative approach involving Grade VII students. Data were collected through classroom observations, documentation of student activities, and analysis of science process skills that emerged during learning, and were analyzed thematically. The results indicate that the 5E Learning Cycle supports student-centered learning and facilitates the gradual development of science process skills. The Engagement stage builds students’ cognitive readiness and motivation. Exploration becomes the main phase for developing basic process skills through experimental activities. Explanation and Elaboration support data interpretation, communication, and application of concepts, while Evaluation functions as a reflection on students’ understanding and learning processes. The study concludes that the 5E Learning Cycle can be effectively implemented in authentic classroom contexts with limited resources and provides both theoretical and practical contributions to process-oriented science learning.